2012
DOI: 10.1038/nature11186
|View full text |Cite
|
Sign up to set email alerts
|

First dairying in green Saharan Africa in the fifth millennium bc

Abstract: In the prehistoric green Sahara of Holocene North Africa-in contrast to the Neolithic of Europe and Eurasia-a reliance on cattle, sheep and goats emerged as a stable and widespread way of life, long before the first evidence for domesticated plants or settled village farming communities. The remarkable rock art found widely across the region depicts cattle herding among early Saharan pastoral groups, and includes rare scenes of milking; however, these images can rarely be reliably dated. Although the faunal ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
268
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 330 publications
(283 citation statements)
references
References 23 publications
10
268
0
5
Order By: Relevance
“…This study sheds additional light on the potential for sherds to absorb lipid, for example, the maximum concentration of absorbed lipid we have ever observed in an archaeological potsherd, from Christian (AD 600-1500) phases of occupation of the site of Qasr Ibrm, Egyptian Nubia, is 17.8 mg g −1 , whilst a further potsherd from Middle Pastoral Levels (ca. 5200-3800 BC) at Takarkori rockshelter, Libya, displayed a concentration of 17.2 mg g −1 (Dunne et al 2012). It has long been known that all residues are subject to a degree of degradative loss during burial, and, consequently, previous experimental work has focussed on the maximum capacity of potsherds to absorb lipids, recording maximum mean values from vessels used to repeatedly boil lamb of 21.8 mg g −1 and containing olive oil, 13.5 mg g −1 (Aillaud 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study sheds additional light on the potential for sherds to absorb lipid, for example, the maximum concentration of absorbed lipid we have ever observed in an archaeological potsherd, from Christian (AD 600-1500) phases of occupation of the site of Qasr Ibrm, Egyptian Nubia, is 17.8 mg g −1 , whilst a further potsherd from Middle Pastoral Levels (ca. 5200-3800 BC) at Takarkori rockshelter, Libya, displayed a concentration of 17.2 mg g −1 (Dunne et al 2012). It has long been known that all residues are subject to a degree of degradative loss during burial, and, consequently, previous experimental work has focussed on the maximum capacity of potsherds to absorb lipids, recording maximum mean values from vessels used to repeatedly boil lamb of 21.8 mg g −1 and containing olive oil, 13.5 mg g −1 (Aillaud 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;Outram et al 2009;Dunne et al 2012;Dunne et al 2016;Roffet-Salque et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the dispersal of modern humans across Africa about 130,000 years ago 4 , the oldest evidence 5 of milking in Africa around 5200 bc and the establishment of the first Saharan state 6 Tadrart Acacus Sabratha Germa southwest ended abruptly in February 2011 with an emergency evacuation on a military aircraft. Before the revolution, I spent three months each year in the desert studying the prehistory of the Messak and nearby Tadrart Acacus mountains, which lie close to the border with Algeria, famous for their 9,000-year-old rock art.…”
mentioning
confidence: 99%